The Dilemmas of Dissidence in East-Central Europe : Citizen Intellectuals and Philosopher Kings - Falk, Barbara J. (Book collections on Project MUSE., 2003)
Discusses one of the major currents leading to the fall of communism. Falk examines the intellectual dissident movements in Poland, Czechoslovakia and Hungary from the late 1960s through to 1989. The author passionately argues that the intellectuals and dissident writers of the region not only contributed mightily to the events themselves, but also collectively bequeathed to the world an oeuvre that constitutes one of the most original, important and useful contributions to political theory today. Besides political theory, Falk provides exciting narrative account of the development of thoughts and actions of those brave intellectuals in the dreary Warsaw, Prague and Budapest of yesteryear.